Bilateral internal iliac artery ligation: the procedure of choice in life threatening postpartum haemorrhage - Darawade, Sameer P.; Wagle, Arti A.; Trivedi, Sneha; Manwani, Saloni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The present study was to assess the indication and study the intraoperative and postoperative complications of bilateral internal iliac artery ligation. Aim of this study was to evaluate the effectiveness of internal iliac artery ligation in arresting postpartum haemorrhage. Methods: This is a retrospective study carried out between January 2015 to December 2018 at Shrimati Kashibai Navale Medical College and General Hospital, Pune. This study included 48 patients with life-threatening PPH. Bilateral internal iliac artery ligation was done by anterior approach in 7 patients and by posterior approach in 41 patients. Results: Intraoperative and postoperative complications were noted in all patients. Of the total patients, 10 required massive blood transfusion and 12 underwent obstetrical hysterectomies (n=12; 25%). Internal iliac vein injury was seen in 1 patient (n=1; 2.08%) and external vein thrombosis was noted in 3 patients (n=3; 6.25%). Maternal mortality was observed in 1 patient due to DIC on day 9 (n=1; 2.08%). The uterine salvage rate was 75%. Conclusions: Internal iliac artery ligation (IIAL) safe, rapid, effective, time tested method of controlling bleeding from genital tract.